Adhesion Properties of Zinc-oxide Filled Epoxidized Natural Rubber/ acrylonitrile-butadiene Rubber Blend Adhesives - Poh Beng Teik (Science Faculty of Chiang Mai University, 2019)
The effect of zinc oxide loading on the adhesion properties of epoxidized natural rubber (ENR 25) / acrylonitrile-butadiene rubber (NBR) blend adhesives was studied using coumarone-indene resin and toluene as tackifier and solvent respectively. Five different loadings, i.e. 10, 20, 30, 40 and 50 phr filler were used in the adhesive formulation. The SHEEN hand coater was used to coat the adhesive on polyethylene terephthalate (PET) at 30 mm and 120 mm coating thicknesses. The viscosity of the adhesive was measured by a Brookfield viscometer. The tack, peel strength and shear strength were determined by a Lloyd adhesion tester operating at 30 cm min-1. Results show that viscosity of the adhesive increases gradually with the filler loading due to the concentration effect of the filler. All the adhesion properties of the ENR 25/NBR adhesive pass through a maximum value at 10 phr filler loading. For the loop tack and peel strength , maximum values occurs at 10 phr zinc oxide loading due to the maximum wettability of adhesive on the substrate. However, for the shear test, the maximum shear strength at the optimum filler loading of 10 phr is attributed to the maximum cohesive strength of the adhesive. In all cases, adhesion properties increase with increasing coating thickness.